2018
DOI: 10.4025/actasciagron.v40i1.39392
|View full text |Cite
|
Sign up to set email alerts
|

<b>Metabolic alterations and X-ray chlorophyll fluorescence for the early detection of lead stress in castor bean (<i>Ricinus communis</i>) plants

Abstract: The remediation of lead-contaminated areas poses a serious challenge to soil chemists because Pb has low solubility in soil. Thus, Pb phytostabilization is considered to be an attractive remediation technique. Castor bean (Ricinus communis) is an oilseed crop known for its tolerance to heavy metals, and our aim was to assess the early detection of Pb toxicity and the effects of Pb on the biomass, photosynthetic pigments, antioxidative enzyme activities, and total soluble proteins of this plant. Specimens were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…In this sense, chlorophyll fluorescence uses information about the photochemical activity of plants, allowing the early detection of environmental stress [11]. This can be done because the chlorophyll molecule is fluorescent, which makes it possible to detect changes in electron transfer at the level of chloroplast membranes through photon dissipation [12]. One of the great advantages of this technique is that it is sensitive to disorders of the photosynthetic cell membrane without destroying the plant tissues of the species under study [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, chlorophyll fluorescence uses information about the photochemical activity of plants, allowing the early detection of environmental stress [11]. This can be done because the chlorophyll molecule is fluorescent, which makes it possible to detect changes in electron transfer at the level of chloroplast membranes through photon dissipation [12]. One of the great advantages of this technique is that it is sensitive to disorders of the photosynthetic cell membrane without destroying the plant tissues of the species under study [13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the content of As and Pb were much higher in roots for both soils. Several studies showed that Pb is mainly accumulated in roots rather than shoots in Rev Bras Cienc Solo 2020;44:e0200081 plants exposed to toxic levels of the metal (Romeiro et al, 2006;Costa et al, 2012;Ma et al, 2016b;Nascimento and Marques, 2018). Likewise, preferential accumulation of As in the roots as compared to shoots have been reported (Melo et al, 2012;Silva et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, by producing Zn-enriched biomass that could be used as fodder (Fassler et al, 2010) or Se-and Boron-rich plants that could be used as organic fertilizers for soils deficient in these elements (Robinson, Green, Chancerel, Mills, & Clothier, 2007;Bañuelos, Arroyo, Dangi, & Zambrano, 2016). The use of bioenergy crops in phytostabilization is also an opportunity to enhance the biomass value (Melo, Guilherme, Nascimento, & Penha, 2012;Nascimento & Marques, 2018), making a strong case for phytoremediation by generating revenue in the land under remediation.…”
Section: Phytostabilizationmentioning
confidence: 99%
“…Given that castor bean oil is inedible, therefore with negligible risk to human or animal contamination, growing the crop in these marginal lands may be an alternative for an economic return resulting from biofuel production. Jatropha curcas, another oilseed crop, is also a viable alternative to revegetate sites contaminated with these metals in tropical regions (Marques & Nascimento, 2013;Nascimento & Marques, 2018). The cultivation of aromatic grasses (Chrysopogon zizanioides, Cymbopogon citratus, and Cymbopogon winterianus) has been proposed as an income source for the local population in sites affected by the Fundão tailing dam rupture in Minas Gerais State, Brazil (Zago, Dores, & Watts, 2019).…”
Section: Phytomanagement: Establishing a New Paradigm?mentioning
confidence: 99%